Antecedents of Financial Management Behavior: Anteseden Pembentuk Perilaku Manajemen Keuangan - Nurisaputri, Adelia Dwi; Fikri, Muhammad Ali; Windikasari, Eka Shinta; Wardana, Made Galih Wisnu (Prosiding University Research Colloquium, 2024)
A person’s level of well-being is measured by many factors, one of which is financial factors. There needs to be basics to help in managing finances so that they can form good financial behavior. The purpose of this study was to find out how knowledge, attitudes, and personality about finance affect financial management behavior. Micro, Small and Medium Enterprises in Yogyakarta were given questionnaires to obtain research data. Research shows that knowledge, attitudes, and personality about finance improve financial management behavior. That way it can be concluded that these three factors can be maximized to form good financial management behavior in running a business.